Conceptualization of crisis situation in a company - Valackienė, Asta; Virbickaitė, Rūta (Journal of Business Economics and Management, 2011)
The paper highlights theoretical construct of crisis situation in a company emphasizing the methodological positions of a social phenomenon. Applying systemic analysis of crisis situation in a company the paper discusses hardly spread social phenomenon, i.e. occurrence and expression of crisis situation in a company. On the basis of retrospective analysis of crisis situation, both crisis environment and bankruptcy features are presented and principal keywords defined with reference to crisis in a company as a social phenomenon and related to its environment: human, company-based, national and global. It shows the complexity of the scientific research object, that brings meaningful input into the analysis of crisis features in company life cycle. The paper aims at discussing and presenting critical reviews of crisis situation interpretations with emphasis on methodological positions of social phenomenon in different disciplines. The differences and links between crisis and crisis situation are also explained. Through explanation of logical construct of the paper, the authors specify crisis concept in a company: distinguishing negative changes in a company, that make the company staff apply crisis communication process and instrumentalities. In the above mentioned context the problem of crisis situation in a company remains significant from psychological, social and economic and managerial perspectives.Article in English.Įmonės krizinės situacijos konceptualizacijaSantrauka. Straipsnis skirtas krizinės situacijos įmonėje teorinio konstrukto analizei, išryškinant šio socialinio reiškinio metodologines pozicijas. Taikant sisteminę krizinės situacijos įmonėje analizę, straipsnyje aptariamas nepakankamai plačiai ištirtas socialinis reiškinys – krizinės situacijos raiškaįmonėje. Retrospektyviai analizuojant krizinę situaciją, atskleidžiami krizės aplinkos ir bankroto bruožai (iliustruojama tiriant kelias įmones) bei patvirtinami pagrindiniai moksliniai teiginiai. Jais remiantis, krizė įmonėje apibrėžiama kaip socialinis reiškinys, kurio raišką galima tyrinėti įvairiose aplinkose ir jos lygiuose: psichologinėje aplinkoje kaip individo, įmonės aplinkoje, valstybės ir globalios aplinkos atžvilgiu.Reikšminiai žodžiai: krizės konceptas, krizės lygiai, krizės indikatoriai, bankrotas.